Integrating canopy and large-scale effects in the convective boundary-layer dynamics during the CHATS experiment - M. M. Shapkalijevski (Atmospheric Chemistry and Physics, 2017)
By characterizing the dynamics of a convective boundary layer above a relatively sparse and uniform orchard canopy, we investigated the impact of the roughness-sublayer (RSL) representation on the predicted diurnal variability of surface fluxes and state variables. Our approach combined numerical experiments, using an atmospheric mixed-layer model including a land-surface-vegetation representation, and measurements from the Canopy Horizontal Array Turbulence Study (CHATS) field experiment near Dixon, California. The RSL is parameterized using an additional factor in the standard Monin–Obukhov similarity theory flux-profile relationships that takes into account the canopy influence on the atmospheric flow. We selected a representative case characterized by southerly wind conditions to ensure well-developed RSL over the orchard canopy. We then investigated the sensitivity of the diurnal variability of the boundary-layer dynamics to the changes in the RSL key scales, the canopy adjustment length scale, Lc, and the β = u*/|U| ratio at the top of the canopy due to their stability and dependence on canopy structure. We found that the inclusion of the RSL parameterization resulted in improved prediction of the diurnal evolution of the near-surface mean quantities (e.g. up to 50 % for the wind velocity) and transfer (drag) coefficients. We found relatively insignificant effects on the modelled surface fluxes (e.g. up to 5 % for the friction velocity, while 3 % for the sensible and latent heat), which is due to the compensating effect between the mean gradients and the drag coefficients, both of which are largely affected by the RSL parameterization. When varying Lc (from 10 to 20 m) and β (from 0.25 to 0.4 m), based on observational evidence, the predicted friction velocity is found to vary by up to 25 % and the modelled surface-energy fluxes (sensible heat, SH, and latent heat of evaporation, LE) vary up to 2 and 9 %. Consequently, the boundary-layer height varies up to 6 %. Furthermore, our analysis indicated that to interpret the CHATS measurements above the canopy, the contributions of non-local effects such as entrainment, subsidence and the advection of heat and moisture over the CHATS site need to be taken into account.